2014
DOI: 10.1111/jgs.13136
|View full text |Cite
|
Sign up to set email alerts
|

Honoring Choices Minnesota: Preliminary Data from a Community‐Wide Advance Care Planning Model

Abstract: Advance care planning (ACP) increases the likelihood that individuals who are dying receive the care that they prefer. It also reduces depression and anxiety in family members and increases family satisfaction with the process of care. Honoring Choices Minnesota is an ACP program based on the Respecting Choices model of La Crosse, Wisconsin. The objective of this report is to describe the process, which began in 2008, of implementing Honoring Choices Minnesota in a large, diverse metropolitan area. All eight l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 15 publications
3
12
0
Order By: Relevance
“…In contrast to these studies, which evaluated decedents, the current study evaluated all patients aged 65 and older with a clinic visit. A recent study describing a community‐wide AD initiative demonstrated 11.6–31.7% AD capture rate in outpatients aged 65 and older at eight institutions . The current study was concordant with this capture rate among living individuals.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In contrast to these studies, which evaluated decedents, the current study evaluated all patients aged 65 and older with a clinic visit. A recent study describing a community‐wide AD initiative demonstrated 11.6–31.7% AD capture rate in outpatients aged 65 and older at eight institutions . The current study was concordant with this capture rate among living individuals.…”
Section: Discussionsupporting
confidence: 88%
“…A recent study describing a community-wide AD initiative demonstrated 11.6-31.7% AD capture rate in outpatients aged 65 and older at eight institutions. 6 The current study was concordant with this capture rate among living individuals.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…HealthPartners leaders are accountable to the board of directors for progress toward nonclinical goals just as they have traditionally been accountable for clinical care goals. Program examples include child-focused activities promoting healthful nutrition and physical activity (43–45), an advance care planning initiative to increase well-being at end of life (46), and a multisectoral campaign to eliminate stigma surrounding mental illness (47). HealthPartners is active in urban initiatives supporting education and health (48) and recently launched a 10-component Children’s Health Initiative with a goal of improving children’s health and well-being from birth through age 5 (49).…”
Section: Opportunities To Improve Community Well-being Exist Within Tmentioning
confidence: 99%